Predicting outcome of assertive outreach across England - Brugha, T; Taub, N; Smith, J; Morgan, Z; Hill, T; Meltzer, H; Wright, C; Burns, T; Priebe, S; Evans, J; Fryers, T (2012)
Background Assertive community treatment for the severely mentally ill is being implemented increasingly internationally. It is unclear whether recommended characteristics of assertive outreach (AO) teams influence care and outcomes. We hypothesised that recommended characteristics of AO teams such as joint health and social care management would predict reduced hospitalisation in the first year of an AO client programme and related outcomes throughout England. Methods A two-stage design was used: a stratified sample of 100 of the 186 'stand-alone' AO teams in England and a systematic sample of clients from each team with stratification for black and ethnic minority patients. Team characteristics, treatment and outcomes were collected from teams. Analyses took account of patients' histories, clustering and ethnic minority over-sampling. Results Under AO the proportion of time spent in hospital following admission decreased. Only 3/1,096 patients went missing in 9 months. Although patient' histories significantly predicted outcomes almost no team characteristics predicted re-admission or other patient outcomes after 1 and 3 years. Ethnic minority clients were more likely to be on compulsory orders only on jointly managed teams (P = 0.030). Multidisciplinary teams and teams not working out of hours significantly predicted that patients received psychological interventions, but only 17% of sampled patients received such treatments. Conclusions Characteristics of AO teams do not explain long-term patient outcomes. Since recommended team characteristics are not effective new models of care should be developed and the process of care tested. Managing teams to implement evidence-based psychological interventions might improve outcomes. © Springer-Verlag 2011.